Native–White Intermarriage and Family in 19th‐century North America. Issue 3 (4th March 2016) - Graybill, Andrew R.
Abstract: Although intimate relationships between Indian peoples and European newcomers to North America ensued from the earliest colonial encounters, they have long been overlooked, especially by comparison to the study of sex between Whites and African Americans. But recently, historians have begun to examine Native–White intermarriage and family, especially in the crucial years between the American Revolution and Reconstruction. Westward expansion produced not only dispossession and removal but also flourishing communities of mixed‐blood peoples, from the Great Lakes to the Pacific Northwest and from the northern Plains to the southern Rocky Mountains. This essay explores five key historiographical interventions made by contemporary scholars – focusing on geography, demography, violence, genealogy, and sovereignty – while suggesting new avenues for academic inquiry.